Immunophenotypic Pattern in Pediatric Acute Lymphoblastic Leukemiain a Tertiary care Hospital in Bangladesh - Jahan, Yesmin Tanjin; Olia Sharmeen Baten; Molla, Md Lutfor Rahman; Imran Habib; Nazneen Sultana; Shabnam Shahidullah; Farhana Rahman; Prodip Kumer; Wahida Nargis; Liza, Noor A Sabah (Sir Salimullah Medical College Journal, 2026)
Background: Acute lymphoblastic leukemia (ALL) is the most common malignancy in children. Diagnosis of ALL is made on the basis of morphology, cytochemistry, immunophenotype and cytogenetics. Immunophenotyping is essential for WHO classification of acute leukemia. It is important for diagnosis, management and prognosis. The aim of the study was to evaluate the immunophenotypic pattern of pediatric ALL. Methods: This cross-sectional study was conducted in the Department of Pediatric Hematology and Oncology in Sir Salimullah Medical College Mitford Hospital, Dhaka, Bangladesh from January 2022 to December 2023. A total of 54 children diagnosed with ALL were included in this study. Results: This study found that out of 54 patients 47 (87%) were male and 7 (13%) were female. B-lineage ALL was found in 49 (90.7%) of the patients and T-lineage ALL was found in 5 (9.3%) patients. This study also found that B-lineage ALL patients were younger with median age six years in comparison to T-lineage ALL. According to French-American- British (FAB) classification L2 subtypes of ALL are more common in T-lineage ALL. Compared with B-lineage ALL higher leukocyte count, CNS involvement and mediastinal mass seem to be the typical features of T-lineage ALL. CD19, CD10, CD20, cCD79a, cCD22 markers were expressed in B-lineage ALL and CD3, CD4, CD5, CD7, CD8 were expressed in T-lineage ALL. Conclusion: ALL is more common in male child. B-lineage ALL is more frequent than Tlineage ALL. T-lineage ALL is associated with FAB subtypes L2 variety, higher leukocyte count, mediastinal and CNS involvement. CD19, CD10, CD20, cCD79a, cCD22 markers were expressed in B-lineage ALL and CD3, CD4, CD5, CD7, CD8 were expressed in Tlineage ALL. Sir Salimullah Med Coll J 2025; 33: 125-131